Endoplasmic Reticulum Stress in Systemic Lupus Erythematosus and Lupus Nephritis: Potential Therapeutic Target - Hui-Yuan Li; Li-Feng Huang; Xiao-Rong Huang; Dan Wu; Xiao-Cui Chen; Ji-Xin Tang; Ning An; Hua-Feng Liu; Chen Yang (Journal of Immunology Research)
Systemic lupus erythematosus (SLE) is a complex autoimmune disease. Approximately one-third to two-thirds of the patients with SLE progress to lupus nephritis (LN). The pathogenesis of SLE and LN has not yet been fully elucidated, and effective treatment for both conditions is lacking. The endoplasmic reticulum (ER) is the largest intracellular organelle and is a site of protein synthesis, lipid metabolism, and calcium storage. Under stress, the function of ER is disrupted, and the accumulation of unfolded or misfolded proteins occurs in ER, resulting in an ER stress (ERS) response. ERS is involved in the dysfunction of B cells, macrophages, T cells, dendritic cells, neutrophils, and other immune cells, causing immune system disorders, such as SLE. In addition, ERS is also involved in renal resident cell injury and contributes to the progression of LN. The molecular chaperones, autophagy, and proteasome degradation pathways inhibit ERS and restore ER homeostasis to improve the dysfunction of immune cells and renal resident cell injury. This may be a therapeutic strategy for SLE and LN. In this review, we summarize advances in this field.